2008
DOI: 10.2460/javma.233.5.767
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of biosecurity and infection control programs at veterinary teaching hospitals

Abstract: Results suggested that differences existed among infection control programs at these institutions. Perceptions of experts regarding program rigor appeared to be skewed, possibly because of a lack of published data characterizing programs at other institutions. Results may provide a stimulus for hospital administrators to better optimize biosecurity and infection control programs at their hospitals and thereby optimize patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
116
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 21 publications
1
116
0
5
Order By: Relevance
“…Paralleling these are reports of the increasing role of MRSA in nosocomial infections in veterinary settings (Seguin et al 1999, Leonard, et al 2006, Weese et al 2007, Benedict et al 2008, McLean and Ness 2008, van Duijkeren et al 2010. A recent study of veterinary teaching hospitals accredited by the American Veterinary Medicine Association (AVMA) found that MRSA was the second most common pathogen (13/31, 42%) associated with nosocomial outbreaks (Benedict et al 2008). However, the interaction between the environment, patients, and hospital personnel in the transmission of MRSA in veterinary hospitals has not been described.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Paralleling these are reports of the increasing role of MRSA in nosocomial infections in veterinary settings (Seguin et al 1999, Leonard, et al 2006, Weese et al 2007, Benedict et al 2008, McLean and Ness 2008, van Duijkeren et al 2010. A recent study of veterinary teaching hospitals accredited by the American Veterinary Medicine Association (AVMA) found that MRSA was the second most common pathogen (13/31, 42%) associated with nosocomial outbreaks (Benedict et al 2008). However, the interaction between the environment, patients, and hospital personnel in the transmission of MRSA in veterinary hospitals has not been described.…”
Section: Introductionmentioning
confidence: 90%
“…Several studies have implicated hospital surfaces contaminated with nosocomial pathogens, including MRSA, in the dissemination of hospital-acquired infections (Rampling et al 2001, Schultsz et al 2003, Hota 2004, Kramer et al 2006, Sexton et al 2006, Boyce 2007, Weber et al 2010, Otter et al 2011. Paralleling these are reports of the increasing role of MRSA in nosocomial infections in veterinary settings (Seguin et al 1999, Leonard, et al 2006, Weese et al 2007, Benedict et al 2008, McLean and Ness 2008, van Duijkeren et al 2010. A recent study of veterinary teaching hospitals accredited by the American Veterinary Medicine Association (AVMA) found that MRSA was the second most common pathogen (13/31, 42%) associated with nosocomial outbreaks (Benedict et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As Comissões de Controle de Infecção Hospitalar (CCIH) em medicina humana são obrigatórias nos hospitais do país (Brasil 1997), com diretrizes e normas bem estabelecidas (Brasil 1998). Porém, em Medicina Veterinária, não há controle dos dados estatísticos sobre a real incidência dessas infecções, devido à ausência das CCIH, que são responsáveis pela vigilância epidemiológica de todos os pacientes, em especial aqueles que apresentam maior risco, como os cirúrgicos (Benedict et al 2008, Weese 2008.…”
Section: Introductionunclassified
“…Other studies have found that impracticality of biosecurity in everyday practice is a key barrier to personal protective equipment use, for example where it restrains safety, time or causes heat stress. 11,20 Benedict et al 3 also suggested veterinarians are inconvenienced by biosecurity practices and that this may prevent veterinarians from performing these practices unless they understand the need and value of them. This suggestion is consistent with cognitive behaviour theories such as the Protection Motivation Theory, which outlines that a person's perceptions of a behaviour's practicality and effectiveness are linked to their motivation and compliance with the behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Overseas, many studies have identified the need for prevention of nosocomial and zoonotic infections in clinical settings. [1][2][3][4][5] In Australia, the emergence of zoonotic Hendra virus has lead to calls for better risk assessment and biosecurity practices of Australian equine veterinarians in the field 6 . The 2007 equine influenza outbreak also raised equine veterinarians' awareness of the need for good biosecurity and hygiene practices to prevent the spread of infectious diseases from client to client.…”
Section: Introductionmentioning
confidence: 99%